Policy Analysis of Edu-Technopreneurship-Based MBKM Implementation in Higher Education: A Case Study of the MBKM Program at Universitas PGRI Madiun - Supri Wahyudi Utomo; Bambang Eko Hari Cahyono; Fida Chasanatun; Muhammad Hanif; Jeffry Handhika; Marheny Lukitasari (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This research aims to analyze the policy of implementing MBKM at Universitas PGRI Madiun (UNIPMA) based on Edu-Technopreneurship. The research method used is the descriptive qualitative approach. The subject of this study is all UNIPMA lecturers, students, and staff. The data collection technique used (1) a survey from the Ministry of Education and Research and Technology that had been adapted to the Edu-Technoprenership-based UNIPMA MBKM program, (2) a survey given to faculty leaders, (3) analysis of the MBKM implementation document. The data were analyzed descriptively. The result shows that UNIPMA already has policies and guidelines for MBKM Edutechnopreneurship activities. The study program also has a curriculum, MBKM guidelines, and standard operational guidelines for implementing MBKM activities according to the characteristics of each study program. Policies and guidelines owned by universities and study programs have been socialized offline and online, but each has not been optimal. There are still lecturers, students, and staff who have not received complete information regarding policies, curriculum, and guidelines related to the implementation of MBKM. It is recommended to formulate policies at the university and faculty level to disseminate policies, curriculum, and other tools related to MBKM edutechnopreneurship. The implementation of MBKM has a positive impact on additional competencies such as skills in solving complex real problems, improving soft skills, and according to future needs. However, there are still 7% of students who are worried that their study period will be longer. With the correct and appropriate MBKM socialization policy, as well as testimonials from MBKM activity participants, it is hoped that the concerns of prospective MBKM participants can be reduced. Students are very interested and enthusiastic in participating in MBKM activities especially to connect their competencies with the industrial world.The form of the internship is the most sought after by students.